2015
DOI: 10.1245/s10434-015-4840-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Treatment After Diagnosis of Recurrent Esophageal Carcinoma Following Esophagectomy with Curative Intent

Abstract: BackgroundStrategies for the treatment of recurrence after initial curative esophagectomy are increasingly being recognized. The aim of this study was to identify prognostic factors that affect survival in patients with recurrence and to evaluate treatment strategies.MethodsA prospective database (2003–2013) was used to collect consecutive patients with esophageal carcinoma treated with initial curative esophagectomy. Locations, symptoms, and treatment of recurrence were registered. Post-recurrence survival wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 29 publications
6
56
0
Order By: Relevance
“…A growing body of literature continues to suggest that oligometastasis may represent tumors with more favorable biology and that these patients may benefit from an aggressive treatment approach aimed at the site of recurrence [13][14][15][16]. For example, several investigators have suggested that surgical treatment of oligometastatic nonsmall cell lung cancer may improve survival [16,17].…”
Section: Commentmentioning
confidence: 99%
“…A growing body of literature continues to suggest that oligometastasis may represent tumors with more favorable biology and that these patients may benefit from an aggressive treatment approach aimed at the site of recurrence [13][14][15][16]. For example, several investigators have suggested that surgical treatment of oligometastatic nonsmall cell lung cancer may improve survival [16,17].…”
Section: Commentmentioning
confidence: 99%
“…It has been found that any form of treatment can significantly improve survival time in patients with oligometastases in the form of fewer than three metastases, although this may be biased by patient selection [18].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy was attributed to the fact that recurrent cases were treated with chemotherapy, meaning that the esophageal cancer death rate subsequently decreased. In previous studies focusing on recurrent esophageal cancer, chemotherapy improved the prognosis of recurrent disease [32][33][34].…”
Section: Discussionmentioning
confidence: 99%